Judicial Sentences and Textual and Terminological Accessibility - Motta, Ester (2021)
This article presents part of the development of a doctoral research in progress in the Graduate Program in Letras of the Federal University of Rio Grande do Sul. The research seeks to generate descriptive data about the language in use in Judicial Sentences of the Special Civil Courts, which are based on principles such as informality and simplicity and were created to expand and facilitate access to Justice. And, considering that many of those who resort to these Courts are people with low income and limited schooling, the reflection promoted is on how, through textual simplification, seen as an intralinguistic translation, one could promote the textual and terminological accessibility of these Judicial Sentences. In order to carry out the analyzes, based on the studies related to textual simplification and through the AntConc, Sketch Engine and Coh-Metrix-Dementia tools, this article analyzes some indexes of cohesion and textual coherence of a corpus of these judicial sentences and compares its lexicon with that of a corpus of texts from Diário Gaúcho and with a reference corpus of written Brazilian popular Portuguese, CorPop. Both represent what can be called everyday written Portuguese. Based on the results of these analyzes, rewriting alternatives that are more appropriate for the adult Brazilian citizen with low schooling and little experience in reading are proposed. Preliminary results suggest that the judicial sentences of these Special Courts have lexical and syntactic patterns that hardly coincide with patterns of everyday written language so that they may hinder their intelligibility for the target audience.